魯迅小説的敍述技巧: The Narrative Technique of Luxun’s Short Stories
<span data-sheets-value=""1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."" data-sheets-userformat=""2":705,"3":"1":0,"9":0,"10":1,"12":0" data-sheets-validation-definition=""1":"1":"1":24,"2":["1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ],"2":"1":"1":["1":4,"6":0,"1":2,"3":"TRIM","4":1,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ,"1":2,"3":"ARRAY_ROW","4":2,"1":2,"3":"ARRAY_LITERAL","4":1,"1":2,"3":"TRIM","4":1,"1":2,"3":"EXACT","4":2,"1":2,"3":"OR","4":1,"1":2,"3":"ARRAYFORMULA","4":1,"1":1,"2":"="],"3":"R0]FTRIM:1]LSLANGUAGE NOTE | Document text in Chinese; abstract also in English.]]LSLANGUAGE NOTE | Document text in Chinese only.]]FARRAY_ROW:2]FARRAY_LITERAL:1]FTRIM:1]FEXACT:2]FOR:1]FARRAYFORMULA:1]S","3":["1":"1":0,"2":1,"3":0,"4":1,"5":1118464,"2":0],"2":"","3":0,"4":1" data-sheets-validation-id="0">LANGUAGE NOTE | Document text in Chinese; abstract also in English. <span data-sheets-value=""1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."" data-sheets-userformat=""2":705,"3":"1":0,"9":0,"10":1,"12":0" data-sheets-validation-definition=""1":"1":"1":24,"2":["1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ],"2":"1":"1":["1":4,"6":0,"1":2,"3":"TRIM","4":1,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ,"1":2,"3":"ARRAY_ROW","4":2,"1":2,"3":"ARRAY_LITERAL","4":1,"1":2,"3":"TRIM","4":1,"1":2,"3":"EXACT","4":2,"1":2,"3":"OR","4":1,"1":2,"3":"ARRAYFORMULA","4":1,"1":1,"2":"="],"3":"R0]FTRIM:1]LSLANGUAGE NOTE | Document text in Chinese; abstract also in English.]]LSLANGUAGE NOTE | Document text in Chinese only.]]FARRAY_ROW:2]FARRAY_LITERAL:1]FTRIM:1]FEXACT:2]FOR:1]FARRAYFORMULA:1]S","3":["1":"1":0,"2":1,"3":0,"4":1,"5":1118464,"2":0],"2":"","3":0,"4":1" data-sheets-validation-id="0">魯迅(1881-1936)是我國現代小説重要的開拓者。他的小説，無論內容、形式、技巧，都突破傳統小説的規範，尤其敍述技巧方面，勇於作種種新的嘗試。他借鑑了西方的敍事觀點理論，靈活變化運用：每一種敍事觀點都加以試驗，相同的敍事觀點又加以變化運用，做成每一篇作品都有不同的形式。 <span data-sheets-value=""1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."" data-sheets-userformat=""2":705,"3":"1":0,"9":0,"10":1,"12":0" data-sheets-validation-definition=""1":"1":"1":24,"2":["1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ],"2":"1":"1":["1":4,"6":0,"1":2,"3":"TRIM","4":1,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ,"1":2,"3":"ARRAY_ROW","4":2,"1":2,"3":"ARRAY_LITERAL","4":1,"1":2,"3":"TRIM","4":1,"1":2,"3":"EXACT","4":2,"1":2,"3":"OR","4":1,"1":2,"3":"ARRAYFORMULA","4":1,"1":1,"2":"="],"3":"R0]FTRIM:1]LSLANGUAGE NOTE | Document text in Chinese; abstract also in English.]]LSLANGUAGE NOTE | Document text in Chinese only.]]FARRAY_ROW:2]FARRAY_LITERAL:1]FTRIM:1]FEXACT:2]FOR:1]FARRAYFORMULA:1]S","3":["1":"1":0,"2":1,"3":0,"4":1,"5":1118464,"2":0],"2":"","3":0,"4":1" data-sheets-validation-id="0">《吶喊》和《彷徨》是魯迅創作小説的結集。本文就兩部小説集中二十五篇小説，逐一分析其敍述技巧；而所謂敍述技巧，主要是敍事觀點的選擇、運用，有時旁及敍述時間的操縱、調度。 Lu Xun (1881-1936) is an important pioneer of Chinese modem fiction. The content, format, techniques of his novels are also breakthroughs to the canonical of traditional Chinese novels. He also made new attempts in his narrative techniques. He used the experience of the narrative viewpoint theory from the western novels and handled them with great flexibility. He experimented on each of the narrative viewpoint and applied them quick-wittedly on the same narrative viewpoint so that each piece of the novels has a different modality. <span data-sheets-value=""1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."" data-sheets-userformat=""2":705,"3":"1":0,"9":0,"10":1,"12":0" data-sheets-validation-definition=""1":"1":"1":24,"2":["1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ],"2":"1":"1":["1":4,"6":0,"1":2,"3":"TRIM","4":1,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ,"1":2,"3":"ARRAY_ROW","4":2,"1":2,"3":"ARRAY_LITERAL","4":1,"1":2,"3":"TRIM","4":1,"1":2,"3":"EXACT","4":2,"1":2,"3":"OR","4":1,"1":2,"3":"ARRAYFORMULA","4":1,"1":1,"2":"="],"3":"R0]FTRIM:1]LSLANGUAGE NOTE | Document text in Chinese; abstract also in English.]]LSLANGUAGE NOTE | Document text in Chinese only.]]FARRAY_ROW:2]FARRAY_LITERAL:1]FTRIM:1]FEXACT:2]FOR:1]FARRAYFORMULA:1]S","3":["1":"1":0,"2":1,"3":0,"4":1,"5":1118464,"2":0],"2":"","3":0,"4":1" data-sheets-validation-id="0">"Cry Out” (’Na Han’) and "Wandering" (‘Pang Wang’) are the two collections of short novels of Lu Xun. This passage focuses on the analysis of the narrative viewpoints of the twenty five masterpieces one by one. The so-called narrative techniques are mainly the choice of narrative viewpoint. He might sometimes takes interest in the control and management of narrative time as well. , journal=人文中國學報, author=曾錦漳, year=2001, month=Sep., pages=53–84